Maternal antiretroviral therapy for the prevention of mother-to-child transmission of HIV in Malawi: maternal and infant outcomes two years after delivery. - Marina Giuliano; Mauro Andreotti; Giuseppe Liotta; Haswell Jere; Jean-Baptiste Sagno; Martin Maulidi; Sandro Mancinelli; Ersilia Buonomo; Paola Scarcella; Maria F Pirillo; Roberta Amici; Susanna Ceffa; et al. (PLoS ONE, 2013)
Background Optimized preventive strategies are needed to reach the objective of eliminating pediatric AIDS. This study aimed to define the determinants of residual HIV transmission in the context of maternal antiretroviral therapy (ART) administration to pregnant women, to assess infant safety of this strategy, and to evaluate its impact on maternal disease. Methodology/principal findings A total of 311 HIV-infected pregnant women were enrolled in Malawi in an observational study and received a nevirapine-based regimen from week 25 of gestation until 6 months after delivery (end of breastfeeding period) if their CD4+ count was > 350/mm(3) at baseline (n = 147), or indefinitely if they met the criteria for treatment (n. 164). Mother/child pairs were followed until 2 years after delivery. The Kaplan-Meier method was used to estimate HIV transmission, maternal disease progression, and survival at 24 months. The rate of HIV infant infection was 3.2% [95% confidence intervals (CI) 1.0-5.4]. Six of the 8 transmissions occurred among mothers with baseline CD4+ count > 350/mm(3). HIV-free survival of children was 85.8% (95% CI 81.4-90.1). Children born to mothers with baseline CD4+ count < 350/mm(3) were at increased risk of death (hazard ratio 2.6, 95% CI 1.1-6.1). Among women who had stopped treatment the risk of progression to CD4+ count < 350/mm(3) was 20.6% (95% CI 9.2-31.9) by 18 months of drug discontinuation. Conclusions HIV transmission in this cohort was rare however, it occurred in a significative proportion among women with high CD4+ counts. Strategies to improve treatment adherence should be implemented to further reduce HIV transmission. Mortality in the uninfected exposed children was the major determinant of HIV-free survival and was associated to maternal disease stage. Given the considerable proportion of women reaching the criteria for treatment within 18 months of drug discontinuation, life-long ART administration to HIV-infected women should be considered.